Risk Factors and Neurologic Outcomes Associated With Resuscitation in the Pediatric Intensive Care Unit - Lee, En-Pei; Chan, Oi-Wa; Lin, Jainn-Jim; Hsia, Shao-Hsuan; Wu, Han-Ping (Frontiers in Pediatrics, 2022)
Objectives: In the pediatric intensive care unit (PICU), cardiac arrest (CA) may be rare but commonly results in high rates of morbidity and mortality. Methods: A retrospective chart review of patients suffering from in-PICU CA with cardiopulmonary resuscitation (CPR) were analyzed from January 2017 to December 2020. Risk factors associated with poor clinical outcomes in children with CA after resuscitation were further analyzed. Neurologic outcomes at discharge were evaluated using pediatric cerebral performance category (PCPC). Results: A total of 223 pediatric patients were collected in this study. Return of spontaneous circulation was attained to 167 (74.8%) patients. In all, only 58 (25%) patients survived to hospital discharge, and 49 (21.9%) of the cohort had good neurologic outcomes. Based on multivariate logistic regression analysis, vasoactive-inotropic drugs usage before CA, previous PCPC scale > 2, underlying hemato-oncologic disease, and total time of CPR were risk factors associated with poor outcomes. Furthermore, we determined the cutoff values of duration of CPR in predicting poor neurologic outcomes and in-hospital mortality in patients caused by in-PICU CA as 17 (min) and 23.5 (min) respectively. Conclusion: Risk factors associated with neurologic outcomes and mortality in children with CA after resuscitation in the PICU were vasoactive-inotropic drugs usage before CA, previous PCPC scale > 2, underlying hemato-oncologic disease, and total time of CPR